PENERAPAN BIMBINGAN KELOMPOK DENGAN METODE DISKUSI BERBASIS ONLINE UNTUK MENGEMBANGKAN KONSEP DIRI POSITIF PESERTA DIDIK SMP KELAS IX - Riezky Amanah B.P; Heris Hendriana; Siti Fatimah (IKIP Siliwangi, 2023)
This study aims to describe the implementation of group guidance services with discussion methode in developing positive self-concepts for class IX students at SMP Karya Pembangunan Pasirjambuonline via WhatsApp. Data collection techniques in this study include observations, interviews and documentation studies. The results demonstrated that students with negative self-concepts who participated were slowly able to understand and develop their positive self-concepts. In this study, the service was conducted three times. The first meeting was held to strengthen the relationship between group members, and the second meeting discussed self-concept, problem identification and existing problem-solving strategies, and in the last meeting evaluation and follow-up were carried out. The results of the service found that students with negative self-concepts who participated in group guidance services with online discussion methods at the SMP Karya Pembangunan Pasirjambuslowly and developed their positive self-concepts. This can be seen from during the service process where students can realize their self-concept.Keywords:Group Guidance, Online Discussion Method, Self Concept.